Atypical fibroxanthoma in a young woman: An unusual case presentation - Melendez, Mark M (Pulsus Group Inc, 2007)
Atypical fibroxanthoma (AFX) is an uncommon neoplasm, identified as a spindle cell tumour that is generally found in elderly patients on sun-exposed areas. The majority of cases of AFX are benign, and metastasis is a rare phenomenon. The first case in the literature of AFX is described in a young woman with no previous risk factors who presented with a three-month history of an enlarging nodule of the left nasal alar. Excision showed the lesion to be composed of hyperchromatic, pleomorphic, vacuolated spindle cells and multinucleated giant cells. The tumour cells stained positive for macrophage-histiocyte antigen alpha(1)-antitrypsin, neurokinin-1, CD68 and alpha(1)-antichymotrypsin. The present case report highlights the importance of correct diagnosis for AFX with adequate excision and by considering the histopathology and immunohisto-chemistry of its clinical differential diagnosis.